Role of CT Imaging for Coronary and Non-coronary Interventions - Marwan, Mohamed; Achenbach, Stephan (Current Cardiovascular Imaging Reports, 2017)
Purpose of Review: Pre-procedural imaging is essential for successful planning and performance of several cardiac interventions. Cardiac computed tomography (CT) is a non-invasive imaging modality capable of providing precise information required for different coronary and non-coronary interventions. The role of cardiac CT for the guidance of different cardiac interventions will be described in this review. Recent Findings: Contrast-enhanced computed tomography imaging is increasingly being used for guiding transcatheter cardiac interventions. Anatomical and functional information provided by CT helps in successful planning and performance of several cardiac interventions. Summary: Over the last decade, the continuous growth of interventional cardiology has been associated with widespread acknowledgment that CT is particularly useful for pre-interventional imaging with increasing implementation in clinical routine.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Cardiac CT; Chronic total occlusion; Chronic total occlusions; Coronary interventions; Left atrial appendage; Structural heart disease; TAVI